Dyretiva: um método para a verificação das restrições temporais em sistemas embarcados - Cadamuro Junior, João (2007)
The Dyretiva is a method used for verifying the time constraints of embedded realtime systems. The verification is performed by monitoring the embedded software when it is running in an embedded hardware. The Dyretiva method takes into account the resource constrained nature of embedded systems and the time bounded nature of real-time systems. The method is comprised by a monitoring approach and a fault model. The monitoring approach defines the physical and the logical interfaces used in the observation of the system under test, as well as the strategies used for an optimized trace data collection. The fault model identifies relationships and components of the system under test that are most likely to have time faults. To demonstrate Dyretiva concepts, a set of support tools called SoftScope has been developed. SoftScope is comprised of a source code pre-instrumentation tool, a source code instrumentation tool, a hybrid monitor, a program for controlling the hybrid monitor, programs for filtering and analyzing trace data, and a graphical presentation tool. The Dyretiva method and the SoftScope tool set are an integral part of the work-inprogress PERF project, which is under development in the LIT (Laboratory of Embedded Systems Innovation and Technology), at the UTFPR (Federal Technological University of Paraná State). The objective of the PERF project is to build a complete environment suitable for the development of embedded and real-time systems.